CHARACTERIZATIONS OF Trichoderma sp. AND ITS EFFECT ON Ralstonia solanacearum OF TOBACCO SEEDLINGS - Sutarman, Sutarman; Jalaluddin, Ahmad Khafidh; Li’aini, Arrohmatus Syafaqoh; Prihatiningrum, Andriani Eko (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2021)
Characterizations of Trichoderma sp. and its effect on Ralstonia solanacearum of tobacco seedlings. This study aims todetermine the molecular-based characteristics of Trichoderma sp. Tc-Jjr-02 and its effect as a biocontrol agent in protecting tobaccoseedlings against bacterial wilt caused by R. solanacearum. The characterization of biocontrol agents was based on morphologicaland molecular data’s observation using microscope and the key of determination. The in vivo experiments was consist of fivetreatments: (1) inoculation of Trichoderma isolates at six hours before R. solanacearum inoculation, (2) inoculation of Trichodermaisolates at six hours after R. solanacearum inoculation (3) simultaneous inoculation of Trichoderma isolates and R. solanacearum,(4) inoculated only with R. solanacearum, and (5) without any inoculation. The experiment was repeated six times. Based onBLAST’s analysis, the Tc-Jjr-02 sequence is in accordance with T. asperellum with 100% Query Cover. Inoculation of T. asperellumTc-Jjr-02 at six hours before and after and simultaneously with pathogens providing protection for young tobacco plants by slowingdown the time for the onset of blight by 100–162%, reducing the symptom index by 56–63%, and increasing the dry weight of plantbiomass by 39–53% compared to tobacco seeds which were only inoculated with R. solanacearum.